Efektifitas Intervensi Keperawatan Tehnik Reiaksasi Progresif Nafas Dalam Dengan Posisi Alternatif Berbaring Terhadap Stabilitas Tekanan Darah Padapasien Stroke Hemorrhagik Fase Sub-Akut Di Irna Medik Penyakit Saraf RSUD Dr. Soetomo Surabaya - Dwi Adji Norontoko, - (2002)
A stroke (also called a cerebrovascular accident or CVA) occurs when blood vessels carrying oxygen and other nutrients to a specific part of the brain suddenly burst or become blocked. When blood fails to get through to the affected parts of the brain, the oxygen supply is cut off, and brain cells begin to die.The other main category of stroke, hemorrhagic stroke, occurs when a blood vessel in or around the brain ruptures, spilling blood into the brain or the area surrounding the brain. Furthermore, the accumulated blood from the ruptured artery soon clots, and displacing normal brain tissue. Whenever become decrease serebral perfusion. The brain lack of oksigens supplay , and last the brain become swelling. It was cause increase intracranial pressure. When this occurs, the cells nourished by the artery fail to get their normal supply of nutrients and cease to function properly. Unconsciousness andhemodynamic disfunction are main problems on the patient hemorrhagic stroke. Hemodynamic disfunction kind of blod pressure disruption and heart beats too. Hemodynamic disfucntion caused by autoregulation disorder, undercontroled on the brain steam secondary medulla oblongata compression, pressure distorsion of fourth ventricle, neck and sternocleidomastoid muscle spasm. and release cortisol hormons. The research leaded to study effectiveness the deep breathing relaxation technical on uprigh lying down , become stabilization of blood pressure of the hemorrhagic stroke patients on subacute fase. The research applied Quasi Experimental .: Pre-Post Test Design. Independent variable is the deep breathing relaxation technical on uprigh lying down. Dependent variable is blood pressure. Structured questionnair.e were administered on data collection and analyzed using t-Test by level of significance on t = 0.01 , or P s 0.01 . Sampling design is consecutive sampling. Sample size was thirteen people ( men and wamen ). Research conclusion is relationship between the deep breathing relaxation technical on uprigh lying down and stabilizati.on of blood pressure of the hemorrhagic stroke patients on subacute fase. Therewas significant effect P= 0.000.